Philippines - Typhoons Ondoy and Pepeng : Post-Disaster Needs Assessment - Main Report - World Bank (World Bank, 2012)
Tropical storm Ondoy (international name Ketsana) hit the Philippines on September 26, 2009, causing widespread flooding Tropical storm Ondoy was quickly followed by typhoon Pepeng (international name Parma). It initially brought powerful winds with gusts of up to 230 km/hr then an extended period of heavy rains, with cumulative rainfall amounts exceeding 1,000 mm in some areas. The resulting river floods have been estimated to have a return period of around 50 years, meaning that statistically speaking, such a rainfall event occurs on average once in every 50 years. Ondoy and Pepeng resulted in large numbers of affected persons and casualties. The Government declared a National Sate of Calamity on October 2nd. The Department of Finance requested development partners to undertake a Post-Disaster Needs Assessment (PDNA) jointly with the Government. In response, development partners organized a team of local and international experts to initiate the Post-Disaster Needs Assessment (PDNA) process for Ondoy and Pepeng with Government agencies. The needs for financing are large, but the cost of doing nothing would be larger still. This PDNA estimates the total cost of recovery and reconstruction at US$ 4.42 billion.